TRP-channels as key integrators of lipid pathways in nociceptive neurons. - Sisignano, M; Bennett, D; Geisslinger, G; Scholich, K (2014)
TRP-channels are the most prominent family of ligand-gated ion channels for pain perception. In sensory neurons, TRPV1-V4, TRPA1 and TRPM8 are expressed and are responsible for the conversion of external stimuli to painful sensations. Under pathophysiological conditions, excessive activity of TRP-channels leads to mechanical allodynia and thermal hyperalgesia. Among the endogenous TRP-channel sensitizers, activators and inhibitors, more than 50 arachidonic acid- and linoleic acid-metabolites from the COX-, LOX- and CYP-pathways, as well as lysophospholipids and isoprenoids can be found. As a consequence, these lipids represent the vast majority of endogenous TRP-channel modulators in sensory neurons. Although the precise mechanisms of TRP-channel modulation by most lipids are still unknown, it became clear that lipids can either bind directly to the target TRP-channel or modulate TRP-channels indirectly by activating G-protein coupled receptors. Thus, TRP-channels seem to be key sensors for lipids, integrating and interpreting incoming signals from the different metabolic lipid pathways. Here, we discuss the specific properties of the currently known endogenous lipid-derived TRP-channel modulators concerning their ability to activate or inhibit TRP-channels, the molecular mechanisms of lipid/TRP-channel interactions and specific TRP-regulatory characteristics of the individual lipid families.